ABUNDANCE OF FISH INDICATORS OF CORAL REEF FAMILY CHAETODONTIDAE IN THE WATERS OF LAGOI BINTAN REGENCY OF RIAU ISLANDS PROVINCE BY : - Marpauang, EkoRinaldi; Siregar, Yusni Ikhwan; Siregar, Sofyan Husein (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTA Study on the abundance of Chaetodontidae, coral cover and relationship of abudance with coral cover were conducted from May - July 2019 in the Lagoi Waters of Bintan Regency of Riau Islands Province. Abudance of fish observed with Underwater Visual Census (UVC) method while coral cover with Reef Check method. Apparently the abundance of Chaetodontidae fish ranged from 313.3 - 603.3 ind/ha whereas coral cover ranging from 46 - 74%.Forthat, abudance of coral fish corelated (r = 0.977) with coral cover, suggest that, there is a very strong relationship between live coral cover and Chaetodontidae fish. Key words :Chaetodontidae, Coral Reef, Lagoi Waters